A study of aerodynamic deaggregation mechanisms and the size control of NanoActive™ aerosol particles - Hubbard, Joshua A. (Kansas State University, 2006)
Large specific surface areas and high concentrations of reactive edge and defect sites make NanoActive™ metal oxide powders ideal chemical adsorbents. These powders are dispersed in aerosol form to remediate toxic wastes and neutralize chemical and biological warfare agents. In the destructive adsorption of toxic chemicals, effective application requires particles be as small as possible, thus, maximizing surface area and number of edge and defect sites. Other applications, e.g. smoke clearing, require particles be large so they will settle in a timely manner. Ideally, particle size control could be engineered into powder dispersion devices. The purpose of this study was to explore particle cohesion and aerodynamic deaggregation mechanisms to enhance the design of powder dispersion devices. An aerosol generator and four experimental nozzles were designed to explore the most commonly referenced deaggregation mechanisms: particle acceleration, particles in shear and turbulent flows, and particle impaction. The powders were then dispersed through the nozzles with increasing flow rates. A small angle light scattering device was used to make in situ particle size measurements. The nozzle designed for impaction deaggregated the NanoActive™ MgO particles to a lesser degree than the other three nozzles, which deaggregated the particles to a similar degree. Flows in three of the four nozzles were simulated in a commercial computational fluid dynamics package. Theoretical particle and aggregate stresses from the literature were calculated using simulated data. These calculations suggest particle acceleration causes internal stresses roughly three orders of magnitude larger than shear and turbulent flows. These calculations, coupled with experimental data, lead to the conclusion that acceleration was the most significant cause of particle deaggregation in these experiments. Experimental data also identified the dependence of deaggregation on primary particle size and agglomerate structure. NanoActive™ powders with smaller primary particles exhibited higher resistance to deaggregation. Small primary particle size was thought to increase the magnitude of van der Waals interactions. These interactions were modeled and compared to theoretical deaggregation stresses previously mentioned. In conclusion, deaggregation is possible. However, the ideas of particle size control and a universal dispersion device seem elusive considering the material dependent nature of deaggregation.
Keywords: Deaggregation; Aerosol particles; Small angle light scattering; Particle size control; Cohesion; Nanostructured; Engineering, Materials Science (0794); Engineering, Mechanical (0548); Physics, Optics (0752)